Children of Patanjala; Revisiting the problem of Baduy origins using Old Sundanese and Old Javanese sources - Gunawan, Aditia (UI Scholars Hub, 2025)
Various theories regarding the origins of the Baduy people have been discussed by scholars. A recent contribution by Robert Wessing and Bart Barendregt (2005) approaches the problem from the broader context of the structure of kingdoms in Java and Pajajaran. The present paper assesses their theory in the light of documentary sources from the fourteenth to the sixteenth century, not only in the Sundanese language but also in Old Javanese. These sources indicate that the religious aspects of Baduy society reflect practices and ideas that seem to have been widespread in early Java and Bali. My approach is to investigate ethnographic and anthropological reports about the Baduy, especially those produced by Europeans at the beginning of the nineteenth century, and to compare them with Old Sundanese and Old Javanese texts from the pre-Islamic period. This study posits that the Baduy, during that specified period, were likely less isolated than they appear in contemporary contexts. Instead, they were integrated into expansive religious networks and state structures. Furthermore, it is argued that the Baduy exhibited a closer affiliation with karəsian beliefs rather than with the hulun hyang community. This alignment underscores a commitment to preserving the primordial fixed conditions and states of existence referred to in pre-Islamic sources as purbatisti and purbajati.